Work Fatigue Due to the Use of High Heels on Promotion Girls Workers - Sunarsieh, Sunarsieh; Anwar, Taufik; Wardoyo, Slamet (JURNAL INFO KESEHATAN, 2023)
During working hours, Sales Promotion Girl (SPG) is standing in a shopping center, which can cause work fatigue. The objective of this study was to examine the work fatigue of SPG who wore high heels in various variations. The research design was cross-sectional, with the research subjects being 60 employees from the SPG in Pontianak Indonesia Mall. The L 77 reaction timer was employed to measure fatigue before and after work. The findings revealed that workers who wore 7 cm heels experienced higher levels of fatigue than those who wore 5 cm or 3 cm heels. The study results revealed no significant difference in fatigue before and after working various variations of high heels (p ≤ 0.001). When wearing high heels, the average level of fatigue increases. However, there was no statistically significant difference in heel height variation on fatigue level (p=0.173). When working in a standing position, wearing shoes with low heels increases comfort and reduces worker fatigue. The results of this study can be used as a starting point for future research by other researchers. Moreover, the findings of this study can also serve as a starting point for other researchers to conduct additional research.